[P043] Dynamic contrast-enhanced magnetic resonance imaging for evaluation of percutaneous transluminal angioplasty outcome in patients with critical limb ischemia: Preliminary results. (August 2018) - Maris, Thomas G; Galanakis, Nikolaos; Kontopodis, Nikolaos; Ioannou, Christos; Karantanas, Apostolos; Tsetis, Dimitrios
Abstract : Purpose: To evaluate foot perfusion in patients with critical limb ischemia (CLI) using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and estimate perfusion parameters changes after percutaneous transluminal angioplasty (PTA). Methods: Eight patients (5 male, median age 68 years, range 58–79 years) with CLI [Rutherford 4 (n = 2), Rutherford 5 (n = 5), Rutherford 6 (n = 1)] were examined. All patients underwent DCE-MRI of the lower calf and foot, 1 day before (pre-PTA) and 1 month after (post-PTA) revascularization. Perfusion parameters such as blood flow (BF), K trans, Kep were analyzed and applied for statistical comparisons. Wilcoxon signed rank tests were used to compare pre and post-PTA perfusion parameters. Results: Revascularization was technically successful in all cases with significant clinical improvement. In addition, the ankle brachial index (ABI) increased from 0.35 ± 0.2 to 0.76 ± 0.25, p  < 0.05. During follow-up (mean duration 18 months), one patient died due to acute myocardial infarction and there were two minor toe amputations. After PTA, mean BF increased from 6.18 ± 3.221 ± 9.788 ± 3.346, K trans increased from 0.063 ± 0.024 to 0.106 ± 0.045 and Kep increased from 0.102 ± 0.026 to 0.145 ± 0.026, p  < 0.05. Conclusions: DCE-MRI may be a useful means for the diagnosis of foot hypo-perfusion. It seems also to be a promising tool for evaluation of PTA outcome, as significant restitution of perfusion parameters was observed after successful revascularization.